Analisis Efektivitas Pelaksanaan Kebijakan Pemerintah Dalam Pemberlakuan Kewajiban Iuran TAPERA (Tabungan Perumahan Rakyat) - Pastika, Dinda Bhawika Wimala; Suryana, Eka Pala; Rizal, Muhammad; Palestina, Firdaus Ayu (Faculty of Law, Diponegoro University, 2025)
New legal products as well as amendments to existing regulations consistently influence the labor sector. One such example is the mandatory contribution to the Public Housing Savings (TAPERA), regulated under Government Regulation No. 21 of 2024 concerning Amendments to Government Regulation No. 25 of 2020, as a derivative regulation of Law No. 4 of 2016 on Public Housing Savings. This study aims to analyze the effectiveness of government policy implementation related to the mandatory TAPERA contributions that must be fulfilled by workers. The research method employed is normative juridical, using both conceptual and statutory approaches. The findings indicate that the implementation of mandatory TAPERA contributions has not been fully effective. From a regulatory perspective, there are still overlaps with labor and social security regulations, creating legal uncertainty. From an implementation perspective, the contribution collection mechanism has not been well integrated into the labor administration system, thus causing technical obstacles. Furthermore, the low level of public understanding and trust in TAPERA affects worker participation. Therefore, although TAPERA has a strong legal foundation, its effectiveness requires regulatory improvement, transparent management, accountable supervision, and adequate legal protection for participants. Moving forward, effectiveness can only be achieved if the policy is implemented consistently and in a coordinated manner, accompanied by continuous public outreach and institutional strengthening as the foundation for implementation.